A stable mixed-valent uranium(v, vi) organic framework as a fluorescence thermometer. Issue 14 (18th June 2021) - Gu, Dongxu; Yang, Weiting; Chen, Huiping; Yang, Yonghang; Qin, Xudong; Chen, Lu; Wang, Song; Pan, Qinhe
Abstract : A stable mixed-valent uranium(v /vi ) organic framework with a 3D interpenetrating structure was synthesized, which can be used as a dual-responsive fluorescence temperature sensor based on the fluorescence intensity and fluorescence lifetime. Abstract : The presence of stable U(v )-containing compounds is important for the study of radionuclides. However, pentavalent uranium is prone to disproportionation, thus U(v )-containing compounds are generally sensitive to air and water. Herein, a stable mixed-valent uranium (U(v )/U(vi ))-based metal–organic framework was synthesized via an in situ hydrothermal method, which features a three-dimensional structure with 3-fold interpenetration. Moreover, it can be used as a dual-responsive fluorescence temperature sensor based on the fluorescence intensity and fluorescence lifetime in the cryogenic range of 77–197 K. The fluorescence enhancement at low temperature (77 K) is about 25 times higher that at room temperature, which is unparalleled in common fluorescent materials. The mechanism can be interpreted as the decrease of nonradiative decay with decreasing temperature. Overall, this finding is beneficial to further our understanding of actinides in this oxidation state and disclose their potential applications.